The Ephemeral Signature of Permafrost Carbon in an Arctic Fluvial Network - Drake, Travis W.; Guillemette, François; Hemingway, Jordon D.; Chanton, Jeffery P.; Podgorski, David C.; Zimov, Nikita S.; Spencer, Robert G. M. (Journal of Geophysical Research: Biogeosciences, 2018)
Arctic fluvial networks process, outgas, and transport significant quantities of terrestrial organic carbon (C), particularly dissolved organic carbon (DOC). The proportion of permafrost C in these fluxes, however, is poorly constrained. A primary obstacle to the quantification of permafrost‐derived DOC is that it is rapidly respired without leaving a unique tracer of its presence. In this study, we investigated the production of bacterial respiratory carbon dioxide (CO2; measured as dissolved inorganic carbon; DIC) during maximum late‐summer thaw in sites spanning a fluvial network (Kolyma Basin, Siberia) to assess whether the biodegradation of permafrost DOC could be detected by the presence of a persistent aged (14C‐depleted) signature on the DIC pool. Using Keeling plot interpretation of DIC produced in bioincubations of river water, we show that bacteria respire varying sources of DOC moving downstream through the fluvial network. Respiration of permafrost (production of aged CO2) was only detected in heavily permafrost thaw influenced sites. In nonpermafrost thaw impacted sites, ambient DIC was modern (14C‐enriched), but rather than precluding the respiration of permafrost OC upstream, we suggest that 14C‐depleted DIC is overwhelmed by modern DIC. Investigation of dissolved organic matter composition via Fourier transform ion cyclotron resonance mass spectrometry highlighted that elevated levels of aliphatic and nitrogen‐containing compounds were associated with the production of aged DIC, providing molecular‐level insight as to why permafrost‐derived dissolved organic matter is rapidly respired. Overall, results from this study demonstrate the difficulty of tracing inputs of a highly reactive substrate to systems with diverse organic matter sources.

Unifying Concepts Linking Dissolved Organic Matter Composition to Persistence in Aquatic EcosystemsUnifying Concepts Linking Dissolved Organic Matter Composition to Persistence in Aquatic Ecosystems - Kellerman, Anne M.; Guillemette, François; Podgorski, David C.; Aiken, George R.; Butler, Kenna D.; Spencer, Robert G. M. (Environmental Science & Technology, 2018)
The link between composition and reactivity of dissolved organic matter (DOM) is central to understanding the role aquatic systems play in the global carbon cycle; yet, unifying concepts driving molecular composition have yet to be established. We characterized 37 DOM isolates from diverse aquatic ecosystems, including their stable and radiocarbon isotopes (δ13C-dissolved organic carbon (DOC) and Δ14C-DOC), optical properties (absorbance and fluorescence), and molecular composition (ultrahigh resolution mass spectrometry). Isolates encompassed end-members of allochthonous and autochthonous DOM from sites across the United States, the Pacific Ocean, and Antarctic lakes. Modern Δ14C-DOC and optical properties reflecting increased aromaticity, such as carbon specific UV absorbance at 254 nm (SUVA254), were directly related to polyphenolic and polycyclic aromatic compounds, whereas enriched δ13C-DOC and optical properties reflecting autochthonous end-members were positively correlated to more aliphatic compounds. Furthermore, the two sets of autochthonous end-members (Pacific Ocean and Antarctic lakes) exhibited distinct molecular composition due to differences in extent of degradation. Across all sites and end-members studied, we find a consistent shift in composition with aging, highlighting the persistence of certain biomolecules concurrent with degradation time.